Highly sensitive timer-based resistance deviation to time converter - S., Zeeshan; A. G., Nadratul; R. , Noor Amalina; D., Sumayyah; T., Rumana; M.O., Myo; K., Sheroz (IIUM Press, 2011)
Based on an inexpensive popular precision timing chip 555 timer, a resistance to time converter is proposed in this paper it is indeed capable of converting resistive and capacitive changes into pulse widths of proportional durations. This converter exhibits a compatibility of wider conversion range with a reasonable level of sensitivity required for industrial applications. The circuit is expected to have application in oil and water supply schemes. Simulated results are shown to be compared with mathematical derivations, both reporting a good level of response matching very closely with the derived results, where a 70% deviation of an elemental value corresponds to a mismatch of 50-70 micro-seconds between derived and simulation results.